Law And Personal Data: Offering Strategies For Consumer Protection In New Normal Situation In Indonesia - Rina Arum Prastyanti; Istiyawati Rahayu; Eiad Yafi; Kelik Wardiono; Arief Budiono (Muhammadiyah University Press, 2021)
Purpose of the study: The benefits of the internet during a pandemic bring opportunities for cybercrimes, such as online data theft and leakage of consumers’ personal data. For this reason, the objectives of this study are 1) to determine the phenomenon of misuse of consumer’s personal data amidst COVID-after19 in Indonesia and 2) to describe strategies in preparing consumer personal data protection as the key to the success of the new normal in Indonesia. Methodology: This study used non-doctrinal research. To describe the phenomenon of misuse of consumers’ personal data amidst COVID-19 in Indonesia, the data were collected by distributing questionnaires to internet users in Indonesia and applying qualitative methods employing survey data collection techniques with stratified multi-stage random sampling technique. Results: It was found that the consumers’ personal data in Indonesia is still unprotected, so the conception adopted by the European Union and the OECD can be used as a reference for Indonesia in making a Law on Personal Data Protection.Applications of this study: To raise the people's awareness in protecting online personal data and encourage the government to educate society on cyber security through the National Cyber and Crypto Agency Novelty/ Originality of this study: This paper analyzes the protection strategy of e-commerce consumers during the new normal situation in Indonesia. The originality is that it discusses amidst Covid 19 cyber security.